Molecular sexing approach using CHD marker for monomorphic birds of Gunung Ledang, National Park, Johor / Jessey Angat - -, Jessey Angat (2016)
Many conservation centers in Malaysia have presented serious problem in sexing monomorphic birds as it does not possess any noticeable morphological differences between sexes. Therefore, it is very hard for them to establish the breeding strategies, conservation and management programs. Polymerase Chain Reaction (PCR) would accurately recognize which gender, by comparing the intron length between the Chromo Helicase DNA-binding gene (CHD) in Z and W chromosomes. A total of 150 individual birds from 5 species were captured from 10 sites by mist nets. The genes were amplified with 1237L/1272H, 2550F/2718R and P2/P8 primer pairs. Result showed sex determination was unambiguous in all species thus, PCR method alone was sufficient for an effective and fast in sex determination except for the Water-breasted Waterhen with 2550F/2718R primer set. The sex ratio between male and female individual was 1:1. The validity and effectiveness of using thoracic feather were tested with the aim to inflict the only potential feather that will be used for future sexing purposes. Adding more samples is vital in the future as to gain more accurate number of individual species in Gunung Ledang, National Park, Johor. In addition, habitat preferences and behavior as well as morphometric measurement in each individual of bird is required as this would assist in the alternative sexing methodology notably using discriminant function along with PCR-based molecular techniques. Overall, the outcome could have a crucial impact on many protection and reintroduction activities based on molecular-based application, hence granting preservation and enhancement of biodiversity in Malaysia.